Pembelajaran Simple Present Tense pada Kelas X SMKN 1 Tapaktuan dengan Metode Drilling - Yulita Halim (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to determine the effectiveness of the drilling method in improving students' understanding of the simple present tense. The study used a Classroom Action Research (CAR) design with the stages of planning, action, observation, and reflection. The subjects were grade X students of SMKN 1 Tapaktuan in the 2025/2026 academic year. Data were collected through observation, interviews, and initial (pre-test) and final (post-test) tests. The results showed a significant increase from an average pre-test score of 60 to 80 in the post-test. This finding confirms that the drilling method is able to improve mastery of English grammar, especially the simple present tense.